Analisis Sarana dan Prasarana Penunjang Pariwisata Halal - Pratistawiningrat, Purba; Karmila, Mila (Universitas Islam Sultan Agung, 2024)
ABSCTRACTHalal tourism or sharia tourism is a tourism activity with the facilities and services provided according to Islamic law. Of the several journals found, there are several journals that do not support the criteria for halal tourism. At present the problem of halal tourism regarding the facilities and infrastructure that support it does not meet the halal criteria determined based on the MUI fatwa 108/DSN-MUI/X/2016 concerning guidelines for organizing tourism based on sharia principles. The purpose of the article he compiled was to find out how the availability of facilities and infrastructure is in accordance with the search for supporting halal tourism. This study uses the analytical literature review method. This is carried out by searching and reviewing journals that have been written by previous authors to be reviewed again with the aim of knowing what things are considered in determining the availability of halal tourism facilities and infrastructure. Based on the results of the analysis, it is known that the facilities and infrastructure supporting halal tourism have not been fulfilled completely because they are still being developed by the tourism manager and the government and it is hoped that halal tourism can be optimal and can attract tourists to get to know more about halal tourism.Keyword: Halal Tourism, Facilites and services, ABSTRAKPariwisata halal atau wisata syariah merupakan kegiatan berwisata dengan adanya fasilitas serta layanan yang disediakan sesuai syariat islam. Dari beberapa jurnal yang ditemukan terdapat beberapa jurnal yang tidak mendukung terkait kriteria pariwisata halal. Pada saat ini permasalahan pariwisata halal mengenai sarana dan prasarana yang mendukung didalamnya belum memenuhi kriteria halal yang ditentukan berdasarkan fatwa MUI 108/DSN-MUI/X/2016 tentang pedoman penyelenggaraan pariwisata berdasarkan prinsip-prinsip syariah. Tujuan dari disusunnya artikel ini adalah untuk mengetahui bagaimana ketersediaan sarana dan prasarana sesuai dengan kriteria penunjang pariwisata halal. Penelitian ini menggunakan metode kajian literature analisis ini dilakukan dengan melakukan penelusuran dan meriview atas jurnal-jurnal yang pernah ditulis oleh penulis sebelumnya untuk dikaji kembali dengan tujuan yaitu untuk mengetahui hal apa saja yang dipertimbangkan dalam menentukan ketersediaan sarana dan prasarana pariwisata halal. Berdasarkan hasil analisis diketahui Sarana dan prasarana penunjang pariwisata halal belum terpenuhi secara lengkap karena masih dalam pengembangan oleh pengelola wisata maupun pihak pemerintah dan diharapkan pariwisata halal tersebut dapat optimal dan bisa menarik para wisatawan untuk lebih mengenal pariwisata halal. Kata Kunci: Pariwisata halal, sarana dan prasarana